De novo biosynthesis of nylon 12 monomer ω-aminododecanoic acid - Jiawei Ge; Ting Wang; Hongwei Yu; Lidan Ye (Nature Communications)
Abstract Nylon 12 is valued for its exceptional properties and diverse industrial applications. Traditional chemical synthesis of nylon 12 faces significant technical challenges and environmental concerns, while bioproduction from plant-extracted decanoic acid (DDA) raises issues related to deforestation and biodiversity loss. Here, we show the development of an engineered Escherichia coli cell factory capable of biosynthesizing the nylon 12 monomer, ω-aminododecanoic acid (ω-AmDDA), from glucose. We enable de novo biosynthesis of ω-AmDDA by introducing a thioesterase specific to C12 acyl-ACP and a multi-enzyme cascade converting DDA to ω-AmDDA. Through modular pathway engineering, redesign and dimerization enhancement of the rate-limiting P450, reconstruction of redox and energy homeostasis, and enhancement of oxidative stress tolerance, we achieve a production level of 471.5 mg/L ω-AmDDA from glucose in shake flasks. This work paves the way for sustainable nylon 12 production and offers insights for bioproduction of other fatty acid-derived products.